Principal's Leadership Style, Library Services Against Student Reading Motivation - Agusalim, Agusalim (CV. Inara, 2022)
Motivation to read is a process of driving behavior or the urge to read. Therefore, this article attempts to measure the role of school principals and library services in increasing reading motivation in elementary schools in Baubau city. This study involved teachers and elementary school students in the Lea-lea sub-district, Baubau City. The questionnaire instrument was used to obtain answers to the relationship between the leadership style of the principal, library services and students' reading motivation. The results of the observation found that there was a deviation in the reading motivation score of elementary school students from the average value, the level of deviation of the Principal's leadership style score from its average value and the level of deviation of the Library Service score from its average value. The design of this research is a quantitative study based on the random sampling method using the normality test of the estimation error and the homogeneity of variance test. The results of the study showed that there was a positive and significant influence between the leadership style of the principal and the reading motivation of elementary school students, there was a positive and significant influence between library services (X2) and reading motivation of elementary school students (Y) and there was a positive and significant influence between the leadership style. Principal (X1) and Library Services (X2) together with Elementary School students' reading motivation (Y).